Identificação, caracterização, atividade biológica e avaliação do mecanismo de ação de peptídeos do néctar floral de Nicotiana sp. - Parra, Aura Lucia Chacón (2022)
Although floral nectar is a rich source of nutrients, it is rarely infected by microorganisms. Defense molecules such as proteins have been identified in this fluid, but defense peptides have been largely overlooked. Thus, the aim of this study was to perform an extensive peptidomic analysis of the ornamental tobacco floral nectar to seek peptides involved in nectar defense. Using LC-MS/MS, 794 peptides were sequenced and characterized. After extensive bioinformatics analysis of physicochemical and biological characteristics as molecular mass, isoelectric point, net charge, hydrophobic ratio, Bowman index and probability of having antifungal and antibacterial activity, six peptides were selected for further synthesis and evaluation of their properties. antimicrobials against phytopathogenic fungi and bacteria. Results of peptide sensitivity tests performed on phytopathogenic microorganisms were that all peptides showed some antimicrobial activity. However, the results were heterogeneous based on the concentration of the peptides and the microorganism. In the case of bacteria, active peptides presented activity at minimal values of 125 and 62 μM, while in fungi, inhibitory activity was obtained at 15 μM. Analysis of the mechanism of action, using fluorescence microscopy, indicated cell membrane damage induced by peptides. The results show that floral nectar is rich in peptides that are responsible for plant defense against different microorganisms, approximately 20% of the identified peptides had predicted antimicrobial activity greater than 60%. These are promising results that lead to a better understanding of floral nectar defense and to possible obtain alternatives biomolecules to combat infectious agricultural diseases.